A Double-Acting Piezoelectric Actuator for Helicopter Active Rotor - Jinlong Zhou; Linghua Dong; Weidong Yang (Actuators, 2021)
An active rotor with trailing-edge flaps is an effective approach to alleviate vibrations and noise in helicopters. In this study, a compact piezoelectric actuator is proposed to drive trailing-edge flaps. The two groups of piezoelectric stacks accommodated in the actuator operate in opposition, and double-acting output can be realized through the differential motion of these stacks. A theoretical model and a finite element model are established to predict the output capability of this actuator, and structural optimization is performed using the finite element model. A prototype is built and tested on a benchtop to assess its performance. Test results demonstrate that the actuator stiffness reaches 801 N/mm, and its output stroke is up to ±0.27 mm when subjected to actuation voltage of 120 V. Agreement between measurements and simulations validates the accuracy of the established models. In addition, actuator outputs in failure modes are measured by canceling the supply voltage of one group of piezoelectric stacks. In this condition, the actuator can still generate acceptable outputs, and the initial position of the output end remains unchanged. Simulations and test results reveal that the proposed actuator achieves promising performance, and it is capable to be applied to a helicopter active rotor.